Mucin-1 expression in endometrium is higher in polycystic ovary syndrome than in normal women (Universa Medicina, 2020)
BackgroundThe polycystic ovary syndrome (PCOS) is caused by endocrine system dysfunction in women. MUCIN-1 (MUC-1) expression is found in endometrial tissues, which leads to implantation process dysfunction because of imbalance of trophoblast adhesion process. This study was conducted to compare endometrial MUC-1 expression between PCOS and normal women considering all existing external variables.MethodsThis cross-sectional study was conducted in General Hospital Dr. Moewardi Surakarta. Endometrial samples were obtained from 30 infertile PCOS women based on Rotterdam criteria, and 30 normal women. Life style and reproductive data such as age, menstrual problems, menstrual cycle, age at menarche, and BMI were collected. Subjects underwent endometrial biopsy in luteinizing hormone (LH) secretion phase LH + 5 days to LH + 10 days for immunohistochemistry (IHC) of MUC-1 expression. An independent-t and multiple linear regression test were used to analyze the data at significance level of p